MANAGEMENT OF MISALIGNED CROWN FRACTURE WITH EXTERNAL ROOF RESORPTION USING MINERAL TRIOXIDE AGGREGATE (MTA) AND CUSTOM CAST POST AND CORE RESTORATION - Rebecca Azary Kuncoro; Yulita Kristanti (Jurnal Teknosains, 2017)
Crown fracture is the most commonly reported traumatic injuries in the permanent dentition. One of the unfavorable response to trauma is the development of external root resorption (ERR). Injuries may also cause tooth angulation changes so it should be treated with a customized cast post and core to produce better aesthetic result and to obtain sufficient compressive strength.The case report describes the use of mineral trioxide aggregate (MTA) as an apical plug to promote periapical healing of an open apex and the use of custom cast post and core to correct the tooth angulation.Case report.A 23-year-old male patient came to RSGM Prof. Soedomo with a chief complaint of a fractured and labial misaligned of upper right central incisor due to trauma 10 years ago. Patient expressed his unwillingness to get orthodontic therapy. Percussion and palpation test showed no discomfort or pain. There was no mobility noticed. Radiograph showed periapical radiolucency and open apex. Tooth was treated with calcium hydroxide dressing and MTA apical plugs were placed in the apical portion of canals. Tooth was restored with custom cast post and core to correct the angulation followed by the placement of an porcelain crown.MTA can be used as apical plug for sealing open apex caused by ERR combined with custom cast post and core for other option for misaligned tooth.